Lexical Structure of the 3 Rd Grade Technology Textbook (Eurasian Journal of Humanities and Social Sciences, 2022)
The article analyzes the lexical category of a technology textbook for third graders. The words in the textbook are recommended to be replaced with words that students can understand, taking into account the age of the school students. Additionally, as a part form of technology textbook for third grades, the coefficient of their usage in the use of words was determined